High temperature thermoelectric properties of nitrogen doped ITO thin films. (February 2020) - Zhao, Xiaohui; Wang, Ruolan; Liu, Yang; Deng, Xinwu; Jiang, Hongchuan; Zhang, Wanli
Abstract: Nitrogen doped indium tin oxide (ITO) and platinum thin films were fabricated on alumina substrate by magnetron sputtering and formed thin film thermocouples (TFTCs) with stencil mask. After annealing in N2 or air, the thermoelectric properties of the TFTCs were calibrated for multiple cycles with different calibration atmospheres. The Seebeck coefficient of ITO thin films at high temperature was obtained. The element segregation and oxygen vacancy was stabilized by the formation of oxynitrides in ITO films. And their effects on the Seebeck coefficient of ITO films was discussed. Highlights: The Seebeck coefficient of ITO films at high temperature is dictated by the oxygen diffusion. The formation of oxynitrides could stabilize the oxygen vacancy of ITO films. The Seebeck coefficient of ITON films demonstrates excellent reproducibility.